Electropolishing and electrolytic etching of Ni-based HIP consolidated aerospace forms: a comparison between deep eutectic solvents and aqueous electrolytes. (4th May 2017) - Goddard, A. J.; Harris, R. C.; Saleem, S.; Azam, M.; Hood, C.; Clark, D.; Satchwell, J.; Ryder, K. S.
Abstract : It is reported in this study that the deep eutectic solvent (DES), (Ethylene glycol)2 (Choline chloride), (2Eg:ChCl) is an effective medium in the electrolytic removal of the Fe-rich layer from Ni-based hot isostatic press (HIP) consolidation and that it is capable of sustaining etching at higher rates and at higher current efficiencies than a comparable aqueous electrolyte formulated from methane sulphonic acid/glycolic acid (MSA/GA). At high etch rates, the surface finish is not as good using 2Eg:ChCl, but high etch rates, current efficiency and excellent surface finish can be obtained from a 90%/10% hybrid mixture of 2Eg:ChCl MSA/GA electrolytes. This study has set out to compare the electropolishing and bulk electrolytic etching of HIP-formed bodies fabricated from RR1000 Ni-based superalloys in aqueous methane sulphonic acid/glycolic acid (MSA/GA) electrolyte and in DES-type ionic liquids. It is shown that the HIP alloy can be effectively removed under mild conditions using DES electrolytes that are of low toxicity, environmentally sustainable, relatively low cost and without the use of strong acids or chemical etchants.